Entrepreneurial Leadership and Entrepreneurial Success: The Role of Knowledge Management Processes and Knowledge Entrepreneurship - Hussain, Nida; Li, Baoming (Frontiers in Psychology, 2022)
Various leadership styles have been widely studied to understand the success process. However, little research has empirically explored how entrepreneurial leadership influences entrepreneurial success. Moreover, the role of the knowledge management processes and knowledge entrepreneurship has been overlooked. Thus, drawn under the light of knowledge-based view theory, this study aims to determine the relationship between entrepreneurial leadership on entrepreneurial success, mediated through knowledge management processes. In addition, for a better understanding study also used knowledge entrepreneurship as a moderator. A quantitative survey method has been employed to collect data from 390 entrepreneurial venture owners, co-founders, and managers in tech-oriented ventures (IT and Software-based) operating in Pakistan. Smart PLS statistical software was used to analyze the impact mechanism of entrepreneurial leadership on entrepreneurial success through the structural equation model. The findings revealed that entrepreneurial leadership style positively influences entrepreneurial success. In addition, knowledge management processes full mediates the relationship between entrepreneurial leadership and entrepreneurial success. Further, knowledge entrepreneurship as a moderator strengthens the relationships among entrepreneurial leadership and knowledge management process. Theoretically, this study has complemented and enriched the research on the influence mechanism between entrepreneurial leadership and entrepreneurial success. Practically, this study has important implications for leaders, managers, and founders to promote the knowledge management processes to achieve entrepreneurial success.